Resolving Jurisdictional Conflicts Between WTO and RTA Dispute Settlement: Toward an Interpretative Approach - Son Tan Nguyen (Bond Law Review)
In the last several decades there has been an exponential growth in the number of Regional Trade Agreements (‘RTA’s). In addition to creating a wide overlap of substantive rights and obligations with the World Trade Organization (‘WTO’), many RTAs are also equipped with legalized dispute settlement mechanisms, which operate independently from the compulsory, automatic and exclusive system of WTO dispute settlement. This parallel operation of substantive commitments and legalized mechanisms may potentially result in conflicts of jurisdiction where a single dispute is submitted simultaneously or consecutively to both fora. It has been well addressed in various studies that if such conflicts arise, there is currently no legal rule that can satisfactorily determine which forum should have jurisdiction. As a result, multiple proceedings appear unavoidable. This article seeks to offer a new way to look into the jurisdictional tension between the WTO and RTAs. It will be argued that in the absence of effective rules to determine jurisdictional priority, principles of treaty interpretation — particularly art 31(3)(c) of the Vienna Convention on the Law of Treaties — provide a practical and useful technique to minimize the negative consequences of multiple proceedings, namely inconsistent interpretations and findings over essentially the same disputes.